2020
DOI: 10.1262/jrd.2020-035
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of long-term repeated treatments of a sustainable GnRH antagonist, degarelix acetate, on caprine testicular functions

Abstract: We investigated the effects of long-term repeated treatments with a sustainable gonadotropin-releasing hormone (GnRH) antagonist, degarelix acetate, on testicular hormonal secretion, size, ultrasound images, histology and spermatogenesis in goats to assess its efficacy as a chemical castration method. Male Shiba goats (3-6 months of age) were treated subcutaneously with degarelix acetate every 4 weeks for 24 weeks. Plasma testosterone and insulin-like peptide 3 (INSL3) concentrations decreased (P<0.05) within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 77 , 89 Also, we have suggested that suppression of pulsatile LH release by a long‐acting GnRH antagonist, degarelix acetate, induced immediate reduction of testosterone secretions followed by INSL3 with a few days delay in male goats, indicating a slower decrease of INSL3 secretion in response to reductions of pulsatile LH release than that of testosterone. 78 , 90 Additions of human chorionic gonadotropin (hCG), which has LH actions, to cultured canine testicular interstitial cells for 18 h stimulated INSL3 release in vitro. 91 On the other hand, in men, serum INSL3 levels did not change by an hCG treatment in a daily blood sample for 8 days, whereas testosterone increased for a few days after treatment, 92 suggesting that the INSL3 secretion is not acutely regulated by LH.…”
Section: Insl3 Secretions In Normal Animals and Humansmentioning
confidence: 99%
See 2 more Smart Citations
“… 77 , 89 Also, we have suggested that suppression of pulsatile LH release by a long‐acting GnRH antagonist, degarelix acetate, induced immediate reduction of testosterone secretions followed by INSL3 with a few days delay in male goats, indicating a slower decrease of INSL3 secretion in response to reductions of pulsatile LH release than that of testosterone. 78 , 90 Additions of human chorionic gonadotropin (hCG), which has LH actions, to cultured canine testicular interstitial cells for 18 h stimulated INSL3 release in vitro. 91 On the other hand, in men, serum INSL3 levels did not change by an hCG treatment in a daily blood sample for 8 days, whereas testosterone increased for a few days after treatment, 92 suggesting that the INSL3 secretion is not acutely regulated by LH.…”
Section: Insl3 Secretions In Normal Animals and Humansmentioning
confidence: 99%
“…77,89 Also, we have suggested that suppression of pulsatile LH release by a long-acting GnRH antagonist, degarelix acetate, induced immediate reduction of testosterone secretions followed by INSL3 with a few days delay in male goats, indicating a slower decrease of INSL3 secretion in response to reductions of pulsatile LH release than that of testosterone. 78,90 Additions of human chorionic gonadotropin (hCG), which has LH actions, to cultured canine testicular interstitial cells for Abbreviations: EIA, enzyme immunoassay; HRP, horseradish peroxidase; LC-MS/MS, liquid chromatography-tandem mass spectrometry; RIA, radioimmunoassay; TRFIA, time-resolved fluorescence immunoassay.…”
Section: Circulatinginsl3inmaleswithnormal Reproductivefunctionsmentioning
confidence: 99%
See 1 more Smart Citation